2013
DOI: 10.1097/dcr.0b013e318270a1a3
|View full text |Cite
|
Sign up to set email alerts
|

Hartmann Reversal

Abstract: Hartmann reversal is associated with significant morbidity; BMI independently predicts complications. Therefore, patients who are obese should be encouraged or even potentially required to lose weight before reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…Park et al argued that age was the most important influencing factor in their study [11] , while high ASA score may reduce the reversal rate [12] . Nonetheless, other study contradicts such claim by arguing that high ASA did not contribute to higher postoperative complication rate [13] . In our study, only 13% of patients had ASA of I while 87% were II or more.…”
Section: Discussioncontrasting
confidence: 57%
“…Park et al argued that age was the most important influencing factor in their study [11] , while high ASA score may reduce the reversal rate [12] . Nonetheless, other study contradicts such claim by arguing that high ASA did not contribute to higher postoperative complication rate [13] . In our study, only 13% of patients had ASA of I while 87% were II or more.…”
Section: Discussioncontrasting
confidence: 57%
“…With reference to the primary surgery, i.e., Hartmann procedure (HP), most of the included studies did not provide detailed data about surgical approach. [2, 11, 17–19, 23, 26–31, 34, 36–40]. In seven studies, all HPs were performed by open surgery, [21, 22, 24, 32, 33, 35] while two articles did include both patients who had received open surgery and patients who had received surgery by laparoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts with relative bibliographies were thus appraised, and a total of 26 studies were eventually deemed suitable for inclusion and data extraction. [2, 11, 17–40] The selection process is given in Fig. 1, while Table 1 describes the general characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The length of intensive care unit (ICU) stay was also significantly ( p = 0.003) shorter in the LG [LG 0 days (0–2); OG 1 day (0–12)]. Significant advantages associated with a laparoscopic procedure were observed for the return to normal bowel function (measured as a clinical parameter by bowel sounds; LG 3 days [2–4]; OG 4 days [2–9]; p < 0.0001), the return to normal diet (LG: 3 days [2–6]; OG 4 days [2–10]; p = 0.001), and in the postoperative continuous use of analgesics (non‐steroidal anti‐inflammatory drug [NSAID] or morphine preparations) in days (LG 7 days [6–10]; OG 12 days [6–30]; p < 0.0001). The length of the overall hospital stay (LOS) was also significantly shorter in the LG, with a median of 9 days (7–14) compared with 15 days (8–163) in the OG ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…In current literature, different results have been reported. Whereas Lin et al [15] found no associations between time to reversal and complications, Pearce et al [16] reported that risks of postoperative complications in reversals were significantly greater in patients who underwent the procedure within 6 months after primary operation versus those whose reversal was delayed longer than 6 months. Conversely, further studies have reported that a longer time to reversal (>9 months) was associated with greater risks of postoperative complications [17–19].…”
Section: Discussionmentioning
confidence: 99%